Test-retest reliability of goniometric measurements of the range of dart-throwing motion - Mitsukane, Masahiro (J Phys Ther Sci, 2019)
[Purpose] To examine the reliability of using a manual goniometer for measuring the range of dart-throwing motion. [Participants and Methods] The range of dart-throwing motion in 24 healthy participants was measured by three raters on the same day, and one rater repeated the measurement on another day of the same week. The stationary arm of the goniometer was placed along the radius, and the moveable arm was placed along the shaft of the second metacarpal, approximately 45° supinated from Lister’s tubercle. All of the participants performed the dart-throwing motion on a plane that passed through the anatomical neutral wrist position, inclined 45° to the orthogonal anatomical plane. [Results] The intra-rater reliability was moderate (0.5–0.75) only for some parameters of the radial extension, and the intraclass correlation coefficients (ICCs) of all other parameters were <0.5. For the inter-rater reliability, the ICCs of all parameters were <0.5. Brand-Altman analysis revealed some fixed biases between the raters, although no proportional bias was observed. [Conclusion] The goniometric measurement procedure examined in this study appeared to be unsuitable for clinical use because of its poor reliability.